Self-management Strategy to Eliminate Academic Procrastination of Junior High School Students - Muhammad, Asrori (Advances in Social Sciences Research Journal, 2023)
The common symptom experienced by junior high school students is academic procrastination. This study aims to examine the self-management strategy to eliminate of academic procrastination of junior high school students. Based on the research result the Manual of Self-management Strategy was developed in order to help counsellors and teachers can administrated easily. There are three combination of techniques: (1) a combination of self-monitoring with self-reward techniques, (2) a combination of self-monitoring with stimulus-control techniques, and (3) a combination of self-monitoring with self-reward and stimulus-control techniques. The present experimental study with a pretest-posttest-control group design found that the combination of self-monitoring with stimulus-control techniques was most effective to eliminate academic procrastination of junior high school students (effect size: 1,87) while the other combination of techniques were less effective.